Plan Estratégico de la Unidad Educativa Particular Liceo Policial "Mayor Galo Miño J." de la ciudad de Ambato, para el período 2008 - 2012. - Cifuentes Zumbana, William Patricio (2009)
In this new era, in which the globalized world innovations proposed necessarily commensurate to time and advances in science and technology, no company in special educational institutions can develop without a new concept of strategic planning. The educational unit Liceo "Myr.Galo Miño", which is projected with a transformative vision should lift its strategic planning and execute strategies based on projects that have been based on human values shared with the trilogy of education; based on mental frameworks exchange, development, critical analysis and human growth from the social dimension and context to go in search of better paths for our students, community and country. The diagnosis was made based on what the tool Foda, and then adjourning the parent technical prioritized and finally obtain the matrix prioritized, in which it has strengths, weaknesses, opportunities and threats in order of priority, to rely on it for the development of strategies for change and the strategic objectives of institutional will to carry out the vision, mission and policies that will contribute significantly to improving the quality of administrative management and providing quality education to our Students, whether in the community. The accountability and improving education that requires society and the education ministry will be reflected in the monitoring, implementation of institutional strategic plan that will be supported with the processes of continuous improvement of ISO 9001-2000 and with the resolute support and participation of all personnel available to the educational unit